PO155 Comparison of cognitive functioning between matched samples of aqp-4 antibody positive and mog antibody nmo patients with healthy controls. (1st December 2017) - Moore, Perry; Wilson, John; Atherton, Michael; Cook, Amy; Mutch, Kerry; Hamid, Shahd; Whittam, Dan; Jacob, Anu
Abstract : Objective: To compare cognitive functioning in aquaporin-4 (AQP4) antibody positive and myelin oligodendrocyte glycoprotein (MOG) antibody positive neuromyelitis optica (NMO patients) matched by age, education and disease duration with matched healthy control (HC) participants. Method: 15 NMO AQP4+, 15 NMO MOG +and 15 HC participants were administered a battery of neuropsychological tests. Test results were combined to give a single composite measure for cognitive functioning. Results: Participants did not significantly differ on age, education level or disease duration. A significant overall effect of group was found on the cognitive composite measure. Post hoc analysis revealed NMO AQP4 +patients scored significantly worse than HCs (Tukey HSD; p=0.05), with no significant difference between NMO MOG+and HCs. Analysis of cognitive subtests identified significant differences on executive functioning testing between the NMO AQP4 +patients and HCs (Tukey HSD; p=0.02) but not between NMO MOG+patients and HCs. Conclusions: Initial data confirms previous findings of evidence for cognitive impairments in NMO patients compared to HCs and indicates that cognitive dysfunction may be greater in AQP4 +patients compared to MOG+ patients, whom did not substantially differ from HCs.